PERANAN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN SEKTOR PUBLIK DAN BISNIS - H. Abdul Rasul (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
Good human resource role in scope of public sector or governance and business world basically is of equal but, responsibility role owned to differ the. Matter caused by because scope work and area wrestled to differ